2016
DOI: 10.1016/j.juro.2016.04.117
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography as a Tool for In Vivo Staging and Grading of Upper Urinary Tract Urothelial Carcinoma: A Study of Diagnostic Accuracy

Abstract: This report describes optical coherence tomography as a real-time, intraoperatively diagnostic modality in the diagnostic evaluation of upper tract urothelial carcinoma. We confirmed the ability of optical coherence tomography to visualize, grade and stage urothelial carcinoma in the upper urinary tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 17 publications
1
41
0
2
Order By: Relevance
“…Owing to the improved definitions for the sensitivity roll-off and confocal point spread function in the newly developed software, the m OCT values for low-grade and high-grade UTUC were substantially higher in the present study. The corresponding sensitivity (83%) and specificity (94%) were similar to the sensitivity (87%) and specificity (90%) of the study by Bus et al [15].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Owing to the improved definitions for the sensitivity roll-off and confocal point spread function in the newly developed software, the m OCT values for low-grade and high-grade UTUC were substantially higher in the present study. The corresponding sensitivity (83%) and specificity (94%) were similar to the sensitivity (87%) and specificity (90%) of the study by Bus et al [15].…”
Section: Discussionsupporting
confidence: 85%
“…Besides technical improvements, the sample size in the present study was substantially larger than in the previous study that proposed a μ OCT cut‐off value . Increasing the sample size of this post‐hoc analysis was achieved by additional inclusion of patients in whom only the histopathologic grade from ureterorenoscopic biopsies was available for comparison.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A follow-on study on a large number of patients (n ¼ 26) by Bus et al further validated the higher attenuation of high-grade lesions (median μ OCT : 3.0 mm −1 ) than low-grade lesions (median μ OCT : 2.1 mm −1 ), demonstrating the feasibility of OCT attenuation for grading low-and high-grade lesions. 88 A recent study on 35 patients by Freund et al 89 demonstrated a consistent contrast in OCT attenuation, as summarized in Table 3.…”
Section: Oncologymentioning
confidence: 82%
“…25). In a larger study, the sensitivity and specificity of OCT for staging urethral tumors was 86.7% and 78.6% respectively and for grading, 91.7% and 78.6%, respectively [178].…”
Section: Urinary Tractmentioning
confidence: 88%